Handbook of commerce and industry in Nigeria (Lagos : The Federal Ministry of Commerce and Industry, 1960)
This Handbook is intended primarily for the use of businessmen, care has been taken to ensure that the information provides is both full and accurate. In this fourth edition, information on the economic life of Nigeria has been brought up to date, and, where necessary, new subject matter has been introduced.
Includes index.
Includes bibliographical references: p. 315-322
aia 04/05/2017
Loans
Keywords: Industries; Nigeria